2016
DOI: 10.4142/jvs.2016.17.2.225
|View full text |Cite
|
Sign up to set email alerts
|

Imaging and surgical outcomes of spinal tumors in 18 dogs and one cat

Abstract: Clinical and magnetic resonance imaging (MRI) findings, histological appearances and surgical outcomes of 18 dogs and one cat with spinal tumors are presented. Medical records of the cases admitted for spinal disorders were reviewed, and cases of spinal tumors that were diagnosed by MRI and confirmed by histological examination were included in this study. T1 weighted, T2 weighted and contrast enhanced T1 weighted images were taken and interpreted to evaluate the spinal tumors. The tumors were diagnosed as: me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
69
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(79 citation statements)
references
References 26 publications
5
69
1
4
Order By: Relevance
“…Surgical gross total tumour removal of vertebral tumours improves the quality of life (Besalti et al 2016). No surgical complications were observed in our case.…”
Section: Discussionsupporting
confidence: 48%
“…Surgical gross total tumour removal of vertebral tumours improves the quality of life (Besalti et al 2016). No surgical complications were observed in our case.…”
Section: Discussionsupporting
confidence: 48%
“…These studies have shown extremely wide variability in survival time, from several days to several years after surgery. Adjunctive therapies were used variably among the dogs in these studies and therefore direct comparison of outcomes and determination of the most effective treatment modalities is challenging . The largest of these case series was reported almost 20 years ago and included 10 dogs with primary vertebral OSA, 4 dogs with metastatic vertebral OSA and 6 dogs with vertebral fibrosarcoma, with a reported survival time ranging from 15‐600 days.…”
Section: Introductionmentioning
confidence: 99%
“…Kippenes and colleagues previously reported MRI findings in dogs with vertebral tumors but only two of the dogs were diagnosed with vertebral plasmacytomas . Magnetic resonance imaging offers several advantages over radiography as a diagnostic imaging modality for investigation of spinal disease, and is considered part of the “gold standard” imaging for human multiple myeloma patients . Veterinary literature describing MRI findings in dogs diagnosed with multiple myeloma is currently lacking.…”
Section: Introductionmentioning
confidence: 99%
“…6 Magnetic resonance imaging offers several advantages over radiography as a diagnostic imaging modality for investigation of spinal disease, and is considered part of the "gold standard" imaging for human multiple myeloma patients. [7][8][9][10] Veterinary literature describing MRI findings in dogs diagnosed with multiple myeloma is currently lacking.…”
mentioning
confidence: 99%